Head Ward Nurse Core Competencies: A Mixed-Method Study - Mozzarelli, Fabio (Fundamental and Management Nursing Journal, 2025)
Introduction: Head ward nurse (HWN) is the one who, within a social and health care organization, plays a key role in the functioning of the ward, organizing work and that co-workers.This study aims to identify the HWN’s core competencies, mapping and grading them according to the level considered most strategic and making them evident through the configuration of a conceptual map defined by the Balanced Scorecard (BSC) model. Methods: This study was conducted in a mixed-method methodology, with a qualitative and quantitative exploratory sequential approach. In the quantitative part, by using the administration of surveys of consecutive convenience samples consisting in doctors, nurses, healthcare worker assistants and therapists staff from the surgical department of the Azienda Unità Sanitaria Locale (AUSL) of Piacenza Italy, 39% of the population of possible respondents for the qualitative part. Another sample of only nurses ward manager from surgery department of AUSL, which is the Local Health Authority of Piacenza, located in the Emilia-Romagna region of northern Italy. It was identified for the quantitative part, 100% of the population of possible respondents. Results: The BSC makes it possible to identify, represent, and measure the performance of nurses especially with a view to enabling the attainment of skills deemed most significant, to be able to have a balance of them within the professional’s portfolio, to ensure the presence of appropriate skills in care settings, and to be able to represent a graduation and eventual measurement of them. Conclusions: The definition, mapping, graduation and representation of the core competencies of the HWN according to the BSC model, allow to make explicit the professional act in order to maintain or improve the exercised performances of the function as well as to lay the basis for their possible evaluation.